Biogeography and taxonomy of racket-tail hummingbirds (Aves: Trochilidae: Ocreatus): evidence for species delimitation from morphology and display behavior - Schuchmann, Karl-L.; Weller, André-A.; Jürgens, Dietmar (Zootaxa, 2016)
We analyzed geographic variation, biogeography, and intrageneric relationships of racket-tail hummingbirds Ocreatus (Aves, Trochilidae). Presently, the genus is usually considered monospecific, with O. underwoodii including eight subspecies (polystictus, discifer, underwoodii, incommodus, melanantherus, peruanus, annae, addae), although up to three species have been recognized by some authors. In order to evaluate the current taxonomy we studied geographic variation in coloration, mensural characters, and behavioral data of all Ocreatus taxa. We briefly review the taxonomic history of the genus. Applying the Biological Species Concept, species delimitation was based on a qualitative-quantitative criteria analysis including an evaluation of character states. Our results indicate that the genus should be considered a superspecies with four species, the monotypic Ocreatus addae, O. annae, and O. peruanus, and the polytypic O. underwoodii (including the subspecies underwoodii, discifer, incommodus, melanantherus, polystictus). In this taxonomic treatment, O. annae becomes an endemic species to Peru and O. addae is endemic to Bolivia. We recommend additional sampling of distributional, ethological, and molecular data for an improved resolution of the evolutionary history of Ocreatus.